Profile Of Childhood Measles Patients At Rsi Siti Rahmah Padang 2020-2022 - Zeffira, Laura; Yulfienti, Elfi; Yulika, Villya; Handayani, Kurnia Maidarmi; Sari, Widia; Khudri, Ghaniyyatul (PT. Hafasy Dwi Nawasena, 2024)
Measles (morbilli), caused by the Morbillivirus, is a highly contagious disease primarily affecting children under 15 years of age. The incidence of measles in Indonesia, particularly in West Sumatra, has been increasing due to declining vaccination coverage. This study provides a descriptive analysis of pediatric measles cases at RSI Siti Rahmah Hospital in Padang, using secondary data from medical records between March 2020 and August 2022. A total of 57 pediatric measles patients were identified. The majority of these patients were aged 5-9 years and predominantly female. Diagnoses were primarily made through anamnesis and physical examination. Most patients had a history of measles vaccination, and more than 50% had good nutritional status. Importantly, 71% of patients with complications had not received measles vaccination. These findings suggest that measles vaccination is likely effective in reducing the severity and complications of the disease in children, highlighting the critical need for maintaining high vaccination coverage to mitigate the impact of measles outbreaks.